Optimalisasi Evaluasi Kinerja Aparatur Sipil Negara: Studi Pengabdian di BKPSDM Kabupaten Majalengka - Leni Rohida; Nursahidin N; Titania T (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Problems encountered by the State Civil Apparatus in Majalengka Regency include manipulation of attendance, indiscipline among civil servants, and the setting of employee performance targets that do not comply with regulations. This study aims to examine the role of the Regional Human Resources Development Agency (BKPSDM) in evaluating the performance of State Civil Apparatus in Majalengka Regency. The descriptive qualitative method used data collected through in-depth interviews, observation, and documentation analysis. The research informants included BKPSDM structural officials, direct superiors of civil servants, and the civil servants who were the objects of evaluation. The results show that BKPSDM plays a role not only as an implementer of performance assessment administration but also as a facilitator in competency development, a provider of personnel information systems, and a guardian of the integrity of the evaluation process. Inhibiting factors in the operationalization of the e-performance evaluation system include limited human resources, low digital literacy capabilities among civil servants, and issues related to delays in data input. This study recommends strengthening the digitalization system, ongoing training, and synergy between BKPSDM and Regional Apparatus Organizations (OPD) as strategic efforts to improve the quality of civil servant performance evaluation within the Majalengka Regency Government.